F4 coffee progenies selection obtained from ICATU group cultivars - Pereira, Thamiris Bandoni; Mendes, Antônio Nazareno Guimarães; Botelho, César Elias; Rezende, Juliana Costa de; Vilela, Diego Júnior Martins; Resende, Marcos Deon Vilela de (Coffee Science - ISSN 1984-3909, 2014)
The objective of this study was to select, for agronomical features and resistance to diseases, F4 generation coffee progenies, obtained from Icatu cultivars. The experiment was conducted in the EPAMIG Experimental Farm (Fazenda Experimental da EPAMIG), in Machado- MG, using progenies derived from the crossing between Icatu with Catuaí Amarelo IAC 62 e IAC 17 cultivars and the IAC 5002 e IAC 5010 progenies. The experimental design was the lattice with four repetitions and the evaluations conducted throughout two years (2010 and 2011). The following features were evaluated: productivity (sacs.ha-1), rust reaction, vegetative vigor, reaction to Cercospora and percentage of beans retained in ‘17 and above’ strainer. REML/BLUP procedures were used, and Mock and Mulamba selection indexes. It was verified, by genetic parameters, that, for productivity, rust reaction and ‘17 and above’ strainder features, the selection of the best progenies would provide increase, with the progenies H 141-17-46 Cova 8, H 141-17-46 Cova 16 and H 141-17-46 Cova 9 provided increases of 362,5, 208,3 and 160,5%, respectively, for the selection from multiple features.